THE IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENT’S LEARNING OUTCOMES AT CLASS XI SMA CERDAS MURNI - Nur Azizah Pulungan; Eidi Sihombing (UNIVERSITAS NEGERI MEDAN, 2014)
ABSTRACT The purpose of this research was to find out the difference of students’ learning outcomes using guided inquiry learning model and conventional learning on static fluids topic at class XI SMA Cerdas Murni. The research method was quasi experiment. The population was all students at class XI SMA semester II SMA Cerdas Murni consist of 4 classes. The sample of this research conduct two classes and consist of 20 students, class XI-1 as experimental class and class XI-2 as control class and define by cluster random sampling. The result that was obtained: posttest average value in experimental class is 74.99 and posttest average value in control class is 65.33. Deviation standard in experimental class is 13.73 and in control class is 10.28. The average value of students’ psychomotor in experimental class is 77.96, and the average value of students’ affective in experimental class is 80.67. Normality test result of both samples is normal and homogeneous, the testing criteria was accepted H0 if -2.024 < t’ < 2.024 and refuse H0 in other condition. Here, H0 was refused because t’ is 2.571 and Ha was accepted. So it can be concluded that the students’ learning outcome using guided inquiry learning model is greater than conventional learning. Keywords : Guided Inquiry Learning Model, Students’ learning outcomes